Recovering full-length viral genomes from metagenomes - Smits, Saskia L.; Bodewes, Rogier; Ruiz-González, Aritz; Baumgärtner, Wolfgang; Koopmans, Marion P.; Osterhaus, Albert D. M. E.; Schürch, Anita C. (Frontiers in Microbiology, 2015)
Infectious disease metagenomics is driven by the question: “what is causing the disease?” in contrast to classical metagenome studies which are guided by “what is out there?”. In case of a novel virus, a first step to eventually establishing etiology can be to recover a full-length viral genome from a metagenomic sample. However retrieval of a full-length genome of a divergent virus is technically challenging and can be time-consuming and costly. Here we discuss different assembly and fragment linkage strategies such as iterative assembly, motif searches, k-mer frequency profiling, coverage profile binning and other strategies used to recover genomes of potential viral pathogens in a timely and cost-effective manner.